Rhinitis is associated with a greater risk of intermittent claudication in adults. Issue 4 (21st January 2014) - Ferrari, M.; Pesce, G.; Marcon, A.; Vallerio, P.; Fratta Pasini, A. M.; de, R.
Abstract Background Chronic inflammatory airway disorders have been reported to be associated with vascular diseases of the heart and central nervous system, but their association with peripheral arterial disease (PAD), a high‐prevalence vascular illness, has not been investigated. Objective To evaluate the association of asthma and rhinitis with intermittent claudication, which is a typical symptom of PAD. Methods The data were collected in the gene–environment interaction in respiratory disease survey, a population‐based, multicase–control study. Participants underwent a standardized interview, skin prick tests and pulmonary function tests. The associations between respiratory diseases and intermittent claudication (i.e. pain in the leg during walking that disappears within 10 min when standing still) were estimated through relative risk ratios (RRR) by multinomial logistic regression models. Results 1174 subjects (aged 20–64 years, of which 52% were females) underwent clinical examinations and were classified into four groups: asthma only (n = 81), asthma–rhinitis overlap (n = 292), rhinitis only (n = 299) and controls (n = 345). The prevalence of intermittent claudication in these groups was, respectively, 2.5%, 3.4%, 6.4% and 2.3%. After adjusting for smoking habits and a wide range of established and potential vascular risk factors, rhinitis without asthma was associated with intermittent claudication (RRR:4.63, 95% CI:1.72–12.5), whereas no significant association was found with asthma alone (RRR:1.45, 95% CI:0.27–7.76) or asthma–rhinitis overlap (RRR:2.89, 95% CI:0.91–9.18). Atopy did not modify the observed association between intermittent claudication and rhinitis. Conclusions Our findings suggest that rhinitis is associated with PAD, a predictor of future cerebrovascular and cardiovascular events, independently of the presence of atopy.